- - علی ثقفی; عبدالرضا تالانه (بررسی‌های حسابداری و حسابرسی, 2006)
This paper empirically investigates, in an emerging market, the role of earnings and book value in equity valuation and uses in the analyses a sample data of 226 Iranian manufacturing firms listed on Tehran Stock Exchange (TSE) for the period of 1991 to 2004. Employing after-tax earnings and beginning-of-year equity book value, both on a per share basis and deflated by the General Consumer Price Index, the paper provides evidences on the negative price-earnings relation and on the role of equity book value as a proxy for the abandonment option value when the firms report losses. Our work contributes in the market-based accounting literature at least in two ways: first, it provides evidence on the equity valuation research in an emerging market with the findings of negative price-earnings relation; and second, it is able to detect the abandonment option role of equity book value by applying in the analysis a proxy for the abandonment option value available to stockholders.